2011
DOI: 10.1371/journal.pone.0023024
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Retinal Nerve Fiber Loss in Patients with Spinocerebellar Ataxia Type 1

Abstract: BackgroundAutosomal dominant spinocerebellar ataxia type 1 is an adult onset progressive disorder with well characterized neurodegeneration in the cerebellum and brainstem. Beyond brain atrophy, few data exist concerning retinal and optic nerve involvement.Objective To evaluate retinal changes in SCA1 patients compared to age and gender matched healthy controls.Methodology/Principal FindingsNine patients with SCA1 were prospectively recruited from the ataxia clinic and were compared to nine age and gender matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 27 publications
7
47
3
2
Order By: Relevance
“…This finding supports volumetric MRI studies that found decreased gray matter in brains of MDD patients (Bora et al, 2012). This finding is also consistent with previous OCT studies that found decreased GCL and IPL volumes in neurodegenerative diseases such as multiple sclerosis (Saidha et al, 2011), spinocerebellar ataxia (Stricker et al, 2011), and Parkinson's disease (Roth et al, 2014). We found significantly lower GCL and IPL volumes in recurrent MDD patients than first episode patients.…”
Section: Discussionsupporting
confidence: 93%
“…This finding supports volumetric MRI studies that found decreased gray matter in brains of MDD patients (Bora et al, 2012). This finding is also consistent with previous OCT studies that found decreased GCL and IPL volumes in neurodegenerative diseases such as multiple sclerosis (Saidha et al, 2011), spinocerebellar ataxia (Stricker et al, 2011), and Parkinson's disease (Roth et al, 2014). We found significantly lower GCL and IPL volumes in recurrent MDD patients than first episode patients.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, RNFL thinning observed in our study showed predominance for the superior and inferior sectors, which could mimic glaucomatous optic disc neuropathy, thus an exhaustive ophthalmologic examination, including intraocular pressure measurement and visual field testing, should be performed in these patients. In that sense, our results differ substantially of the ones published by Stricker et al, 8 who reported a temporal fibre affection in SCA-1, resembling pathology found in toxic or mitochondrial optic nerve diseases. Thus, the physiopathology of the neuro-opthalmologic degeneration in SCA-3 seems to be more similar to the observed in Alzheimer's and Parkinson's disease rather than in the SCA-1 and toxic or mitochondrial optic nerve diseases.…”
Section: Discussioncontrasting
confidence: 86%
“…Loss of the temporal RNFL was documented in mitochondrial optic neuropathies such as Leber hereditary optic neuropathy or dominant optic atrophy; and a mitochondrial pattern has also been proposed for PD. 10,12,13 Temporal RNFL thinning was also reported in autosomal recessive cone-rod dystrophy, spinocerebellar ataxia type 1 and multiple sclerosis. 12,14,15 Other than a mitochondrial pattern, localised breakdown of oxidative defence mechanisms and sensitivity of the temporal RNFL to early damage and subclinical disease activity were also suggested.…”
Section: Discussionmentioning
confidence: 90%
“…10,12,13 Temporal RNFL thinning was also reported in autosomal recessive cone-rod dystrophy, spinocerebellar ataxia type 1 and multiple sclerosis. 12,14,15 Other than a mitochondrial pattern, localised breakdown of oxidative defence mechanisms and sensitivity of the temporal RNFL to early damage and subclinical disease activity were also suggested. 12,15 More evidence is needed to understand the mechanism of sectoral thinning of the RNFL.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation